2017
DOI: 10.1177/1091581816682224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Components of PM2.5 Collected in Japan on the Respiratory and Immune Systems

Abstract: Epidemiologic studies have reported that particulate matter with aerodynamic diameters ≤2.5 μm (PM) affect respiratory diseases, including asthma. The components and/or factors of PM that contribute to the exacerbation of asthma have not been identified. We investigated the effects of extracts of PM collected in Japan on the respiratory and immune systems. PM was collected from an industrial area and an urban area in December 2013. Airway epithelial cells and immune cells were exposed to aqueous or organic ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
(46 reference statements)
1
30
0
Order By: Relevance
“…IL-6 and IL-8 are the two most prominent pro-inflammation mediators (Martin et al 1997;Richman-Eisenstat et al 1993). Our previous study (Honda et al 2017) based on Kawasaki and Fukuoka have shown that organic extracts had more pro-inflammatory effect via IL-6 than aqueous extracts. As the IL-6 and IL-8 expression did not increase at all in the present study, we did not observe any noticeable pro-inflammatory effect by any extract.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…IL-6 and IL-8 are the two most prominent pro-inflammation mediators (Martin et al 1997;Richman-Eisenstat et al 1993). Our previous study (Honda et al 2017) based on Kawasaki and Fukuoka have shown that organic extracts had more pro-inflammatory effect via IL-6 than aqueous extracts. As the IL-6 and IL-8 expression did not increase at all in the present study, we did not observe any noticeable pro-inflammatory effect by any extract.…”
Section: Discussionmentioning
confidence: 95%
“…CD86 is an important and sensitive cell surface molecule for PAHs, as we recently have observed (Chowdhury et al 2017). Moreover, our previous studies revealed aqueous extract from Kawasaki and Fukuoka were able to increase the CD86 expression on the cells (Honda et al, 2017). Hulette et al, 2005 showed that aqueous soluble chemicals including nickel sulphate and hydroquinone are capable to induce CD86 expression in human dendritic cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…120 121 It has also been shown that differences in DEP (a heterogeneous product with regional component variability) have differing effects on IL-6, with organic components having a predominantly stimulatory effect and non-organic components inhibiting IL-6 production. 87 IL-4 and IL-8 also increase in patients with asthma with DEP exposure, with the former showing particular elevation during acute exacerbations. 122 123 In addition to stimulating T2-high inflammation, DEP also appears to independently suppress common mediators of T2-low inflammation.…”
Section: Reviewmentioning
confidence: 95%